Irma Vep [videorecording (DVD)] - Assayas, Olivier; Assayas, Olivier; Zhang, Manyu; Zhang, Keyi, 1969-; Léaud, Jean-Pierre, 1944-; Richard, Nathalie, 1962- (Criterion collection, 2021)
A Hong Kong action-movie star arrives in Paris to play the latex-clad lead in a remake of Louis Feuillade's classic silent crime serial Les vampires. What she finds is a behind-the-scenes tangle of barely controlled chaos as egos clash, romantic attractions simmer, and an obsessive director drives himself to the brink to realize his vision.